PENGARUH PAJAK REKLAME DAN PAJAK PENERANGAN JALAN TERHADAP PENDAPATAN ASLI DAERAH KOTA BEKASI - Dr. Adelina Suryati, SE., M.Ak., CMA., CBV. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This study aims to determine whether there is an effect of the Advertising Tax and Street Lighting Tax on the Bekasi City Original Revenue during the period from 2015 to 2020. The sample selection in this study used the purposive sampling method with predetermined criteria obtained for 5 years so that the total sample used is 72 data. The type of data used is secondary data obtained from the Dispenda (Regional Revenue Service). The results of this study indicate that the Advertising Tax has a positive and significant effect on Regional Original Income with a significant level of 0.000, stating that the H1 hypothesis is accepted. Street Lighting Tax has a positive and significant effect on Regional Original Revenue with a significant level of 0.002, stating that the hypothesis H2 is accepted. Advertising tax and street lighting tax together have a significant and significant impact on local revenue.